Utilization of Information Technology to Improve Transparency in Social Fund Distribution in Local Government in Indonesia: Pemanfaatan Teknologi Informasi untuk Meningkatkan Transparansi Penyaluran Dana Sosial dalam Pemerintahan Daerah di Indonesia - Amelia, Nadya Amelia; Fitrianto, Fitrianto (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
The distribution of social funds by local governments plays a vital role in Indonesia's social welfare system. However, in practice, the distribution process still faces various challenges, such as mistargeting, delays in disbursement, and low accountability. Amid rapid developments in information technology, there is a significant opportunity to leverage digital systems to address these issues. This article aims to comprehensively examine the role of information technology in enhancing the transparency of social fund distribution at the local government level. Using a literature review method, the article analyzes the implementation of information technology through the Social Welfare Information System Next Generation (SIKS-NG), mobile applications such as Sapawarga, the use of WhatsApp bots, and digital transparency dashboards. The findings indicate that integrating technology can improve process efficiency, accelerate data verification, and strengthen public engagement in social oversight. Nevertheless, challenges such as limited digital infrastructure, low technological literacy, and uneven regional commitment to digital transformation remain obstacles that must be addressed. This article highlights the importance of policy support, human resource capacity building, and cross-sector synergy as key factors for the successful digitalization of social fund distribution